The Effectiveness of Offline and Online Classes in Language Learning at Universities Majoring in English Education - Afifah, Andariyatul; Fikri, Dzul (Universitas Cokroaminoto Palopo, 2023)
In this contemporary era, technology's influence on education is profound. Online teaching, in addition to traditional offline classes, has become prevalent. This study explores the preferences of 16 English students at the Islamic University of Malang regarding online and offline classes. The research employs a mixed-method approach, analyzing questionnaire data quantitatively and qualitatively. Results indicate a clear preference for offline learning due to its perceived effectiveness, better understanding, and enhanced engagement, mainly attributed to face-to-face interactions with instructors. Consequently, students favor offline classes over online ones.